Endoscopic Ultrasound-Guided Radiofrequency Ablation (EUS-RFA) of the Pancreas in a Porcine Model - Monica Gaidhane; Ioana Smith; Kristi Ellen; Jeremy Gatesman; Nagy Habib; Patricia Foley; Christopher Moskaluk; Michel Kahaleh (Gastroenterology Research and Practice)
Backgrounds. Limited effective palliative treatments exist for pancreatic cancer which includes surgery or chemotherapy. Radiofrequency ablation (RFA) uses high frequency alternating current to ablate diseased tissue and has been used to treat various tumors. In this study, we evaluated a prototype probe adjusted to the EUS-needle to perform EUS-RFA to permit coagulative necrosis in the pancreas. Methods. Five Yucatan pigs underwent EUS-guided radiofrequency ablation of the head of their pancreas. Using an EUS-needle, RFA was applied with 6 mm and then 10 mm of the probe exposed at specific wattage for preset durations. Results. Only one pig showed moderate levels of pancreatitis (20% proximal pancreatitis). The other animals showed much lower areas of tissue damage. In 3 of the 5 pigs, the proximal pancreas showed greater levels of tissue injury than the distal pancreas, consistent with the proximity of the tissue to the procedure site. In 1 pig, both proximal and distal pancreas showed minimal pancreatitis (1%). There was minimal evidence of fat necrosis in intra-pancreatic and/or extra-pancreatic adipose tissue. Conclusion. EUS-guided RFA of the pancreatic head with the monopolar probe through a 19-gauge needle was well tolerated in 5 Yucatan pigs and with minimal amount of pancreatitis.